Self-employment, educational attainment, and hypertension among Black women and men - Bell, Caryn N.; Tavares, Carlos D.; Owens-Young, Jessica L.; Thorpe, Roland J. (Frontiers in Epidemiology, 2022)
BBackground: Self-employment is generally associated with better health outcomes and educational attainment can shape self-employment. Yet, Black Americans are less likely to be self-employed and analyses of self-employment and health among Black Americans are few. The aim of this study was to determine how educational attainment moderates the associations between self-employment and hypertension among Black adults. Methods: Using data from the 2007-2018 National Health and Nutrition Examination Survey, participants who self-identified as non-Hispanic Black (n=2,855) were categorized as 1) employees with no self-employment income, 2) employees with self-employment income, or 3) having full-time self-employment. Modified Poisson regressions and multiplicative interaction terms were used to determine whether educational attainment moderated the associations between self-employment and measured hypertension (i.e. 140/90 mm Hg or anti-hypertensive medication). Results: Most participants were employees with no self-employment income (81.9%), but 11.8% were employees reporting some self-employment income and 6.3% were self-employed full-time. About two in five (40.9%) had hypertension. Having full-time self-employment was associated with lower rates of hypertension compared to those who were employees (risk ratio=0.82, 95% confidence interval=0.67-0.98), and educational attainment moderated the associations among Black men such that part-time self-employment was associated with high rates of hypertension among Black men who had not completed high school. Conclusions: These results suggest full-time self-employment is associated with lower rates of hypertension among Black adults, but that part-time self-employment may elevate rates of hypertension among Black men depending on educational attainment. Future studies should assess pathways between self-employment and hypertension by educational attainment among Black Americans.